Not All Shocks Are Created Equal: Assessing Heterogeneity in the Bank Lending Channel - Nogueira, Gil; Farinha, Luísa; Blattner, Laura (Management Science, 2024)
We provide evidence that the yield impact of unconventional monetary policy is not a sufficient statistic to measure the strength of the bank lending channel of unconventional monetary policy. As a laboratory, we study three major positive events in the European sovereign debt crisis—the Greek debt restructuring (private sector involvement (PSI)), outright monetary transactions (OMT), and quantitative easing (QE)—using credit registry and security-level bank balance sheet data from Portugal, a country that was directly exposed to all three events. Even though the price of sovereign debt increased by substantially more after the PSI and OMT announcements, only QE led banks to reduce their net sovereign debt holdings and had statistically and economically significant effects on lending to firms and households. The differential effect on banks’ behavior reflects two forces. First, lower bank capitalization levels during the PSI and OMT episodes as well as disincentives to sell sovereign bonds because of their collateral value in the European Central Bank’s long-term refinancing operation facilities reduce the effectiveness of the recapitalization channel. Second, only QE involved direct asset purchases by the central bank and thereby induced a portfolio rebalancing channel from sovereign debt to loans. This paper was accepted by Victoria Ivashina, finance. Funding: The contribution by G. Nogueira to this paper has been prepared under the Lamfalussy Fellowship Program sponsored by the European Central Bank. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2023.00104 .